Educating tomorrow’s citizens: Globalization and gender equality in European young people - Elisa Caponera; Laura Palmerio (Culture e Studi del Sociale)
The present study investigates young peoples’ attitudes towards gender equality across 14 countries who participated in The International Civic and Citizenship Study (ICCS) 2016. The main aim of the present study is to verify whether students’ background variables, civic knowledge and civic self-efficacy contribute to explaining the attitudes towards gender equality. The relationship between these variables was evaluated using a structural equation modeling approach. Data from 50,000 students representative of grade 8 popula-tion from 14 European countries who participated in ICCS 2016 were analysed. A mediation analysis with structural equation modeling assessed the direct and indirect effects of the immigrant background and socio-economic and cultural background on attitudes towards gender through the mediation of civic knowledge and civic self-efficacy. The results showed the role of civic knowledge in mediating the effect of socio-economic background on gender equality. These findings suggest that school policy invests on improving civic knowledge at school.